Silencing, Urban Growth Machines, and the Obama Presidential Center on Chicago's South Side - Schwarze, Tilman; Wilson, David (Frontiers in Sustainable Cities, 2022)
Recent research on growth machines, in a prominent theme, has focused on how mobilized discourses promote urban redevelopment projects. Pushed to the margins, in this work, has been the issue of how alternative growth visions and voices are silenced or muffled. This article examines the notion of “silencing” in urban growth discourses. Silencing, it is argued, should not be understood as censorship but rather as attempts by growth machines to relativize the importance of critical and dissent voices in redevelopment projects. We believe that to understand how redevelopment projects operate and transform (urban) spaces, such rhetorical peripherialization is as important as pro-growth discourses. In developing this argument, the article focuses on the case study of the Obama Presidential Center (OPC) on Chicago's Southeast Side. An OPC growth machine consisting of the Obama Foundation, the city mayor, the University of Chicago, and a coalition of local business and community organizations practices this simultaneity of offering their voice and undercutting alternative voices in adroit ways. Race, it is argued, is at the center of this systematic suppression. The OPC development provides an important example of how current redevelopment in cities across the global west currently proceeds.